Information Imprecision - Ball, Ryan T.; Cuny, Christine (The Accounting Review, 2021)
ABSTRACT This study develops and applies a model-implied measure of information imprecision. We define information imprecision as the degree of noise in investors' prior beliefs about the firm's asset value based on the information set that is currently available. We present a model of credit default swap (CDS) spreads in which the term structure is a function of information imprecision. We exploit observable CDS spreads with short and long maturities to extract an empirical measure of information imprecision. We then examine the moderating role of our measure in two settings. First, we show that the equity market response to credit rating changes increases in the level of information imprecision before the announcement. Second, we show that bond-market professionals' ability to charge a premium to smaller investors, relative to larger investors, increases in the issuing firm's information imprecision. This evidence illustrates the broad applicability of our model-implied measure of information imprecision. JEL Classifications: D82; G14; G24.